JINGLE, a JCMT legacy survey of dust and gas for galaxy evolution studies – I. Survey overview and first results. Issue 3 (14th September 2018) - Saintonge, Amélie; Wilson, Christine D; Xiao, Ting; Lin, Lihwai; Hwang, Ho Seong; Tosaki, Tomoka; Bureau, Martin; Cigan, Phillip J; Clark, Christopher J R; Clements, David L; De Looze, Ilse; Dharmawardena, Thavisha; et al.
ABSTRACT: JINGLE is a new JCMT legacy survey designed to systematically study the cold interstellar medium of galaxies in the local Universe. As part of the survey we perform 850 µm continuum measurements with SCUBA-2 for a representative sample of 193 Herschel -selected galaxies with M * > 10 9  M⊙, as well as integrated CO(2–1) line fluxes with RxA3m for a subset of 90 of these galaxies. The sample is selected from fields covered by the Herschel- ATLAS survey that are also targeted by the MaNGA optical integral-field spectroscopic survey. The new JCMT observations combined with the multiwavelength ancillary data will allow for the robust characterization of the properties of dust in the nearby Universe, and the benchmarking of scaling relations between dust, gas, and global galaxy properties. In this paper we give an overview of the survey objectives and details about the sample selection and JCMT observations, present a consistent 30-band UV-to-FIR photometric catalogue with derived properties, and introduce the JINGLE Main Data Release. Science highlights include the non-linearity of the relation between 850 µm luminosity and CO line luminosity (log  L CO(2–1)  =  1.372 log L 850 –1.376), and the serendipitous discovery of candidate z > 6 galaxies.